PERAN MANAJERIAL KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA ORGANISASI - Shofa Fuadi; Urip Suwarniti; Noor Miyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of the research is to analyze the principal’s managerial role in developing organizational culture at SD Negeri 01 Mulyoharjo. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The results of the research indicate that the principle’s managerial role is very important in developing organizational culture at SD Negeri 01 Mulyoharjo. While the indicators of the principal’s managerial role include: developing school organizations based on its needs, creating a conducive school culture for students, managing school facilities and infrastructure, and utilizing advances in information technology as an improvement in learning. The research concludes that the principal's managerial role has an important role in the success of developing organizational culture at SD Negeri 01 Mulyoharjo. This can be seen in the aspect of developing school organizations based on its needs, including the culture of reading short letters of the Qur'an and Asmaul Husna before learning and the culture of Friday Market, Friday Healthy, Friday Blessed, and also Friday Cheerful. In the aspect of creating a conducive school culture for students, it is implemented by getting used to smiling and greeting, respecting each other, and appreciating each other among school residents. In the aspect of managing school facilities and infrastructure, it is implemented by facilitating student habituation activities. Then, in the aspect of utilizing advances in information technology as an improvement in learning, it is implemented by utilizing technology in learning.